1997
DOI: 10.1099/00222615-46-12-979
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to  -Lactam Antibiotics in Bacteroides Spp.

Abstract: Bacteroides spp., particularly B. fragilis, are well-recognised bacterial pathogens. Production of the typical P-lactamases of Bacteroides restricts the therapeutic use of P-lactam agents mainly to the P-lactamase inhibitor combinations and carbapenems. These compounds have the advantage of broad-spectrum activity and the ability to combat polymicrobial infections. Resistance of Bacteroides spp. to P-lactam antibiotics appears to be increasing, largely because of an overall increase in P-lactamase activity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 87 publications
1
24
0
1
Order By: Relevance
“…Expression of the group 3a, class B metallo-â-lactamase encoded by the silent cfiA chromosomal gene required the location of an IS immediately upstream (Arpin et al, 2002). Edwards (1997) reported that various strains of B. fragilis that produced â-lactamases were resistant to the action of benzylpenicillin and cefoxitin and displayed moderate resistance to imipenem. However, the â-lactamases of these micro-organisms were unable to hydrolyse either cefoxitin or imipenem in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the group 3a, class B metallo-â-lactamase encoded by the silent cfiA chromosomal gene required the location of an IS immediately upstream (Arpin et al, 2002). Edwards (1997) reported that various strains of B. fragilis that produced â-lactamases were resistant to the action of benzylpenicillin and cefoxitin and displayed moderate resistance to imipenem. However, the â-lactamases of these micro-organisms were unable to hydrolyse either cefoxitin or imipenem in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…fragilis is naturally resistant to some â-lactam antibiotics, including monobactams and temocillin, because of the poor affinity shared by its PBPs for these compounds (Edwards, 1997). The PBPs of Bacteroides spp.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation of ␤-lactam activity and PBP affinity in B. fragilis has not been straightforward, partly because there are conflicting results from investigations into the numbering and molecular masses of PBPs from this bacterium. Most studies were done by labeling cells or cell extracts with a labeled antimicrobial and analyzing the results by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (82,83,298). The completion of the genome sequence of B. fragilis allowed a more complete analysis, and seven putative PBP genes were identified.…”
Section: Mechanisms Of Antimicrobial Resistancementioning
confidence: 99%
“…The most important mechanism of ␤-lactam resistance in Enterobacter and Bacteroides strains is the production of chromosomally encoded ␤-lactamases (10,11). Most Bacteroides fragilis enzymes are constitutive cephalosporinases or penicillinases that are inhibited by clavulanic acid (18), while the chromosomally encoded cephalosporinases of Enterobacter strains are inducible enzymes that are not inhibited by clavulanic acid (11).…”
mentioning
confidence: 99%
“…Expandedspectrum cephalosporins are more likely to select resistant strains of Enterobacteriaceae than are other ␤-lactams (23,30,35), while piperacillin (PIP)-tazobactam (TAZ) (the combination of PIP and TAZ is abbreviated PT) appears to suppress the selection of derepressed mutants (20). Very little data are available on the selection of ␤-lactam resistance in B. fragilis strains (10,14,18,37).…”
mentioning
confidence: 99%